YouTube Live Streamer Sustainability:: Presence, Interactivity, and Attractiveness on Viewer Flow Experience. - Dio Doni Harson; Hujjatullah Fazlurrahman; Fresha Kharisma; Achmad Kautsar (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study analyzes the effects of social presence, interactivity, and attractiveness on the flow experience of YouTube Live viewers in Indonesia. Despite the rapid growth of digital broadcasting, sustaining optimal audience engagement remains a challenge, necessitating further investigation into its communicative determinants. Employing an explanatory quantitative design, data were collected from 100 active viewers via purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) within the Stimulus-Organism-Response (S-O-R) framework. The findings indicate that social presence, interactivity, and attractiveness exert a significant positive effect on viewers' flow experience, with streamer attractiveness emerging as the strongest predictor. Ultimately, this study highlights live streaming not merely as an entertainment tool but as a dynamic digital communication space. The results emphasize that fostering two-way communication and a supportive online environment is vital for content creators to sustain audience immersion in new media platforms.